Global burden of mental health problems among children and adolescents during COVID-19 pandemic: An umbrella review. (November 2022) - Hossain, M. Mahbub; Nesa, Fazilatun; Das, Jyoti; Aggad, Roaa; Tasnim, Samia; Bairwa, Mohan; Ma, Ping; Ramirez, Gilbert
Highlights: The COVID-19 pandemic has critically impacted mental health of children and adolescents. We synthesized evidence from 17 reviews with medium to high methodologic quality as per the JBI checklist. The current evidence suggests a high prevalence common mental disorders among children and adolescents. Socio-demographics, lifestyle, and pandemic experiences influenced mental health outcomes. Multilevel interventions are needed to address psychosocial impacts of COVID-19 in young people. Abstract: Mental health problems among children and adolescents are increasingly reported amidst the coronavirus disease (COVID-19) pandemic. In this umbrella review, we aimed to synthesize global evidence on the epidemiologic burden and correlates of child and adolescent mental health (CAMH) problems during this pandemic from existing systematic reviews and meta-analyses. Adopting the Joanna Briggs Institute (JBI) methodology, we evaluated 422 citations and identified 17 eligible reviews with medium to high methodological quality. Most of the reviews reported a high prevalence of anxiety, depression, sleep disorders, suicidal behavior, stress-related disorders, attention-deficit/hyperactivity disorder, and other mental health problems. Also, factors associated with CAMH such as age, gender, place of residence, educational attainment, household income, sedentary lifestyle, social media and internet use, comorbidities, family relationships, parents' psychosocial conditions, COVID-19 related experiences, closure of schools, online learning, and social support were reported across reviews. As most studies were cross-sectional and used nonrepresentative samples, future research on representative samples adopting longitudinal and intervention designs is needed. Lastly, multipronged psychosocial care services, policies, and programs are needed to alleviate the burden of CAMH problems during and after this pandemic.